(untitled) (Eurasian Journal of Engineering and Technology, 2024)
Lithium-ion batteries (LIBs) have changed the storage of energy in a major way, and so they are now considered an extremely important technology in electronic powered devices such as EVs (EVs), consumer electronics, and renewable energy storage systems. They have, though, under different conditions of use, had slower capacity in general due to both the increased and decreased reactions and the mechanical units that were consequently eroded in the course of their use and storage. These are cyclic aging and calendar aging. Cycle aging occurs when batteries are repeatedly charged and discharged. And calendar aging means a gradual loss of performance even when the battery is not actively being used. Both types of aging are affected by several factors such as temperature, charge level, and usage pattern. This article focuses on how these processes affect performance and lifetime by reviewing the main mechanisms that contribute to battery aging. We also explore different models used to estimate the state of health (SOH) of batteries and estimate how long they will last. By examining empirical, semi-empirical and physics-based models, we aim to provide a clear understanding of the factors that lead to lithium-ion battery degradation and the methodologies available to accurately predict battery performance over time.